2021
DOI: 10.1051/0004-6361/202039696
|View full text |Cite
|
Sign up to set email alerts
|

ALMA multiline survey of the ISM in two quasar host–companion galaxy pairs atz> 6

Abstract: We present a multiline survey of the interstellar medium (ISM) in two z > 6 quasar host galaxies, PJ231−20 (z = 6.59) and PJ308−21 (z = 6.23), and their two companion galaxies. Observations were carried out using the Atacama Large (sub-)Millimeter Array (ALMA). We targeted 11 transitions including atomic fine-structure lines (FSLs) and molecular lines: [NII]205 μm, [CI]369 μm, CO (Jup = 7, 10, 15, 16), H2O 312 − 221, 321 − 312, 303 − 212, and the OH163 μm doublet. The underlying far-infrared (FIR) continuum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 264 publications
4
39
0
Order By: Relevance
“…In Fig. 7, we compare the observed [C ii]/[C i] and CO(7-6)/IR luminosity ratios in individual sources from our sample with other high-redshift quasars and SMGs (from Weiß et al 2003;Riechers et al 2009;Bradford et al 2009;Ivison et al 2010;Cox et al 2011;De Breuck et al 2011;Danielson et al 2011;Wagg et al 2012;Salomé et al 2012;Walter et al 2012;Weiß et al 2013;Riechers et al 2013;Rawle et al 2014;Leipski et al 2014;Decarli et al 2014;Venemans et al 2017a;Zhao et al 2020;Pensabene et al 2021) as well local galaxies (based on the compilation in Rosenberg et al 2015) and with the predictions from the models presented in Fig. 6.…”
Section: Physical Properties Of the Cold Ismmentioning
confidence: 99%
See 2 more Smart Citations
“…In Fig. 7, we compare the observed [C ii]/[C i] and CO(7-6)/IR luminosity ratios in individual sources from our sample with other high-redshift quasars and SMGs (from Weiß et al 2003;Riechers et al 2009;Bradford et al 2009;Ivison et al 2010;Cox et al 2011;De Breuck et al 2011;Danielson et al 2011;Wagg et al 2012;Salomé et al 2012;Walter et al 2012;Weiß et al 2013;Riechers et al 2013;Rawle et al 2014;Leipski et al 2014;Decarli et al 2014;Venemans et al 2017a;Zhao et al 2020;Pensabene et al 2021) as well local galaxies (based on the compilation in Rosenberg et al 2015) and with the predictions from the models presented in Fig. 6.…”
Section: Physical Properties Of the Cold Ismmentioning
confidence: 99%
“…This assumption allows us to directly compare our observations with the line and continuum luminosity predictions of Photo-Dissociation Regions (PDRs) and X-ray Dominated Regions (XDRs). The models are based on the analysis presented in Pensabene et al (2021) and briefly summarized here. We use the CLOUDY radiative-transfer code (version c.17.01;Ferland et al 2017) to predict the line emission of a single plane-parallel semi-infinite cloud impinged by a radiation field in both the PDR and XDR regimes.…”
Section: Physical Properties Of the Cold Ismmentioning
confidence: 99%
See 1 more Smart Citation
“…The Planck/HIFI, Hershell/HerMES, H-ATLAS and South Pole Telescope far-infrared/sub-millimetre surveys show that a fair fraction (several percent) of the high-z sub-millimetre-bright galaxies are magnified by gravitational lensing (Ade et al, 2016;Spilker et al, 2016, as well as references therein; Hodge and da Cunha, 2020). Nonetheless, and except for the relatively strong CO and H 2 O lines (Yang et al, 2016;Pensabene et al, 2021), rare are the cases where the magnification is large enough to allow a clear detection of molecular lines from the intervening galaxies, or from the background quasar itself. Besides the detections in a handful of lensed quasars (e.g., APM08279+5255) of a few lines of HCN, HNC and HCO + (García-Burillo et al, 2006;Guélin et al, 2007), one has essentially to rely on source stacking methods to barely detect more molecular species (Spilker et al, 2014;Reuter et al, 2020).…”
Section: Molecules In the Distant Universementioning
confidence: 99%
“…Grey dots are galaxy-integrated values from SHINING (Herrera-Camus et al 2018) and black are from GOALS (Díaz-Santos et al 2017;Lutz et al 2016;Lu et al 2017). Tan dots are a selection of high-z line detections: J1342+0928 (Venemans et al 2017;Bañados et al 2019;Novak et al 2019), SPT0311-58 (Marrone et al 2018), PJ231-20 (Pensabene et al 2021), HFLS3 (Riechers 2013), PJ308-21 (Decarli et al 2019;Pensabene et al 2021), G09.83808 (Zavala et al 2018;Rybak et al 2020), J2310+1855 (Shao et al 2019;Li et al 2020), BR1202-0725 (Decarli et al 2014;Lu et al 2017;Lee et al 2019Lee et al , 2021, SMMJ02399 (Weiß et al 2007;Ivison et al 2010;Ferkinhoff et al 2011), Cloverleaf (Weiß et al 2003;Ferkinhoff et al 2011), SDP.11 (Lamarche et al 2018, and MIPS J1428 (Iono et al 2006;Hailey-Dunsheath et al 2010Sturm et al 2010). In the spatially resolved SHINING galaxies, a sample of nearby galaxies that includes star-forming galaxies, AGN host galaxies, and LIRGs, Herrera-Camus et al (2018) found the trend of decreasing line/L FIR strongest for singly ionized lines like [NII]122µm and [CII]158µm and weakest for neutral [OI]146µm and [OI]63µm.…”
Section: Line Deficitsmentioning
confidence: 99%